Patient’s satisfaction regarding directly observed treatment short course under RNTCP in a district of North India - Srivastava, Kuldeep; Gupta, Abhishek; Saxena, Ruchi; Sharma, R. P.; Midha, Tanu (International Journal Of Community Medicine And Public Health, 2017)
Background: In 2015, RNTCP covered a population of 1.28 billion. A total of 9132,306 TB suspects were examined by sputum smear microscopy and 14, 23, 181 cases were registered for treatment. Most peripheral unit under the RNTCP network is the designated microscopy centre (DMC) which serves a population of around 100,000 (50,000 in tribal and hilly areas). Treatment compliance and patients satisfaction is important concern for quality service success of RNTCP. Objectives of this study were to assess the treatment compliance and patient’s satisfaction regarding directly observed treatment short course chemotherapy (DOTS). Methods: It was an observational study conducted among DMCs of Kanpur district. Multistage random sampling technique was used for selection of DMC in both rural and urban area. 300 subjects interviewed in this study. Results: Most of the study subjects (87%) were satisfied with the services provided at the DMC. Compliant status was better in rural DMC (94.50%). Non-compliance was more in urban DMC (18.4%). Majority of the study subjects (67%) were satisfied due to availability of free medicines at the centres. Difficulty to come on alternate days was the most common reason for dissatisfaction among study subjects (43.6%) followed by wastage of time (23.1%). Conclusions: About 13 percent patient was not satisfied with DMC services. Among urban DMCs 18.4 percent patient were not compliant where it was 5.5 percent among rural DMCs. About 22.0 percent patient was unaware about duration of treatment. Whereas important reason for dissatisfaction with service was ‘difficulty to come on alternate day’.